The Lost Books of Jane Austen - Barchas, Janine (Book collections on Project MUSE., 2019)
"The author traces the significant yet underappreciated historical role that mass-market paperbacks of Jane Austen's books have played in making her the celebrated author she is today. This is a work of bibliography and of literary history. The author has amassed a large collection of rare and forgotten Austen volumes with rich, colorful, and sometimes gaudy covers that are featured, selectively, as figures in the book"--Provided by publisher.